Biosynthesis of a Novel Ginsenoside with High Anticancer Activity by Recombinant UDP-Glycosyltransferase and Characterization of Its Biological Properties - Dandan Wang; Yan Jin; Hongtao Wang; Chenwei Zhang; Yao Li; Sathiyamoorthy Subramaniyam; Jae-Kyung Sohng; Nam-In Baek; Yeon-Ju Kim (Molecules)
UDP-glycosyltransferases (UGTs) contribute to catalyzing the glycosylation of numerous functional natural products and novel derivatives with improved bioactivities. UDP-glucose sterol glucosyltransferase (SGT) is normally involved in the synthesis of sterol glycosides in a variety of organisms. SGT was derived from Salinispora tropica CNB-440 and heterologously expressed in Escherichia coli BL21 (DE3). Novel 12-O-glucosylginsenoside Rh2 was identified using HPLC, high-resolution MS (HR-MS), and NMR analysis. The cell viability assay was performed on 12-O-glucosylginsenoside-treated AGS stomach cancer, HeLa cervical cancer, U87MG glioma, and B16F10 melanoma cell lines. Protein structure modeling, molecular docking, and dynamics simulations were performed using AutoDock 4.2 and GROMACS 2020.1 software. The SGT gene is comprised of 1284 nucleotides and codes for 427 amino acids. The 12-O-glucosylginsenoside Rh2 may be a potential anticancer agent due to its potent viability inhibition of cancer cells. Structural analysis showed critical perspectives into the intermolecular interactions, stability, and binding energetics of the enzyme–ligand complex, with outcomes complementing the experimental data, thereby deepening our understanding of the structural basis of SGT-mediated glycosylation and its functional implications. This report presents a novel ginsenoside, 12-O-glucosylginsenoside Rh2, utilizing reshuffled SGT derived from S. tropica, and provides a promising candidate for anticancer drug research and development.